Analisis Isi Kuantitatif Perlakuan Body Shaming dalam Film Imperfect (Studi Kasus dalam Film Imperfect : Karier, Cinta dan Timbangan) - Meutia Galuh Utami; Rhafidilla Vebrynda (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2023)
Movies were created not only to entertain but also to convey the messages depicted in them. There are many movies that raise social issues. An issue becoming a trend is about body shaming. This issue is still considered trivial by Indonesian people even though the impacts is huge for the victims. One of the movies that raises the issue of body shaming is the movie